E-Wom, E-Trust dan Keluarga serta Pengaruhnya Terhadap Keputusan Pembelian Online Generasi Z Di Kota Pekanbaru - Hayani, Nurrahmi (MUI Kota Pekanbaru, 2023)
This research aims to identify the influence of e-wom, e-trust and family on online purchasing decisions of generation Z in the city of Pekanbaru. This research involved 120 people belonging to generation Z. Samples were taken using a purposive random sampling technique. Data was obtained through distributing questionnaires whose validity and reliability had previously been tested. To test the hypothesis, multiple linear regression analysis, partial significance test (t test) and simultaneous significance test (f test) and determinant coefficient test were carried out. The results of data processing show that simultaneously e-WOM, e-trust and family have a significant influence on online purchasing decisions, but partially only the e-WOM and e-trust variables have a significant influence while the family variable does not have a significant influence on the Z generation's online purchasing decisions in the city of Pekanbaru.